STUDI INTERIOR WARNA PADA RUANG PERPUSTAKAAN (Studi kasus: Perpustakaan Taman Imsail Marzuki) - Wibowo, Nurifqa Wisista; Melanira, Astria (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
n Interior, besides building design, layout and furniture used, color is one of the main aspects. Coloris the basic element of a design that is most expressive and has a meaning and psychological effect given byeach color. Some color patterns have planning and design influences that can accentuate the surface andtextural characteristics of buildings. giving color to the interior of the library space can provide thecharacteristics of the existing space in the library. This study aims to find out how important color is for theinterior of the library space, as well as to find out the appropriate color criteria for the interior space in thelibrary. in this study the method used describes and examines all data and other information from directand indirect observation. This analysis uses qualitative methods by collecting data and then analyzing itand comparing the results with information obtained from the literature. It is hoped that this research willprovide input regarding the appropriate colors in an interior space, especially the library room, and obtaininformation on the psychological effects of existing colors